Variation in Tracheal Reintubations Among Patients Undergoing Cardiac Surgery Across Washington State Hospitals - Khandelwal, Nita; Dale, Christopher R.; Benkeser, David C.; Joffe, Aaron M.; David Yanez, Norbert; Treggiari, Miriam M. (Journal of cardiothoracic and vascular anesthesia, 2015)
The objectives of this study were to examine the variation in reintubations across Washington state hospitals that perform cardiac surgery, and explore hospital and patient characteristics associated with variation in reintubation. Retrospective cohort study. All nonfederal hospitals performing cardiac surgery in Washington state. A total of 15,103 patients undergoing coronary artery bypass grafting or valvular surgery between January 1, 2008 and September 30, 2011. None. Patient and hospital characteristics were compared between hospitals that had a reintubation frequency≥5% or<5%. Multivariate logistic regression was used to compare the odds of reintubation across the hospitals. The authors tested for heterogeneity of odds of reintubation across hospitals by performing a likelihood ratio test on the hospital factor. After adjusting for patient-level characteristics and procedure type, significant heterogeneity in reintubations across hospitals was present (p = 0.005). This exploratory analyses suggested that hospitals with lower reintubations were more likely to have more acute care days and teaching intensive care units (ICU). After accounting for patient and procedure characteristics, significant heterogeneity in the relative odds of requiring reintubation was present across 16 nonfederal hospitals performing cardiac surgery in Washington state. The findings suggested that greater hospital volume and ICU teaching status were associated with fewer reintubations.